A comparative study on normal and high sugary corn genotypes for evaluating raw material quality and enzyme consumption during dry-grind ethanol production / Md Zabed Hossain - Md Zabed , Hossain (2016)
Agronomic and biochemical characteristics of four high sugary corn genotypes (HSGs) and four parent field corn lines (PFCs) were determined to evaluate raw material quality. Subsequently, the effects of kernel sugars on the enzyme requirements, fermentable sugar and ethanol yield, and co-product quality were investigated. Major agronomic characteristics differed among the corn genotypes. Sugar accumulation in the kernels showed a negative correlation with flowering time (FT), grain filling period (GFP) and black layer maturity (BLM). These findings showed that the genotypes exhibiting lower FT, GFP and BLM would have higher amounts of sugars. HSGs contained higher amounts of total soluble sugars (TSS) and lower amounts of starch than the respective PFCs. As a result, a significant negative correlation was observed between kernel starch and sugar content. TSS content in HSGs ranged between 4.43-6.72% in 2012 and 4.64-7.47% in 2013, while it varied in PFCs between 0.76%-1.36% in 2012 and 0.85-1.27% in 2013. Kernel starch ranged between 66.34-69.85% in HSGs and 67.37-72.08% in PFCs in 2012, and 65.89-70.41% in HSGs and 68.69-73.61% in PFCs in 2013. Conventional hydrolysis under four enzyme loads showed that HSGs produced optimum concentration of reducing sugars (RS) while consuming an enzyme load of 3.0 kg/MT, whereas PFCs required 4.0 kg/MT for maximum sugar yield. Conventional fermentation was conducted by simultaneous saccharification and fermentation (CSSF) technique using an initial solid load 250 g/L. Ethanol concentration varied between 98.7-112.5 g/L in HSGs and 80.8-86.8 g/L in PFCs when enzyme load was 3.0 kg/MT. As the enzyme load increased to 4.0 kg/MT, ethanol concentration reached 102.3-113.1 g/L in HSGs and 85.1-99.5 g/L in PFCs. During granular starch hydrolysis (GSH), RS yield in HSGs did not vary significantly above the enzyme load 1.5 kg/MT, while for the PFCs it did not show a significant increase above a higher enzyme load, ranging between 2.0 and 2.5 kg/MT. The final ethanol concentration after granular starch hydrolysis and simultaneous fermentation (GSHSF) with an initial solid load 300 g/L, ranged from 15.25% to 17.5% (v/v) in HSGs and 11.66% to 13.65% in PFCs at the enzyme load 1.5 kg/MT. Ethanol concentration increased to 16.49–17.94% in HSGs and 14.32–16.85% in PFCs as the enzyme load increased to 2.0 kg/MT. Ethanol concentration showed a negative correlation with kernel starch, whereas, a positive correlation was observed between kernel sugars and ethanol yield. The average yield of distiller’s dried grains with soluble (DDGS) among the corn genotypes ranged from 25.07% to 32.44% for CSSF and 26.97% to 31.69% for GSHSF. Among the biochemical components in DDGS, starch content varied significantly between PFCs and HSGs, and the two enzyme doses used for fermentation. Other components in DDGS for both HSGs and PFCs were well within the values reported in the literature. In conclusion, the study has shown that higher kernel sugar in the corn genotypes is able to improve raw material quality for dry-grind ethanol production as it has the potential to reduce enzyme consumption and produce enhanced amounts of ethanol.